Strategies of Islamic Religious Education Teachers in Shaping Students' Attitudes of Dicipline and Responsibility at SMPN 2 Colomadu - Luciana, Dita; Inayati, Nurul Latifatul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Islamic Religious Education has a strategic role in shaping the character of students, especially discipline and responsibility attitudes that are the basis for success in the learning process and social life. This study aims to describe and analyze the strategies of Islamic Religious Education teachers in shaping student discipline and responsibility attitudes at SMP Negeri 2 Colomadu. This research uses a qualitative approach with a case study type. The research subjects were Islamic Religious Education teachers, while data collection was carried out through observation, in-depth interviews, and documentation. Data analysis is carried out through data reduction, data presentation, and conclusion drawing by maintaining the validity of the data. The results of the study show that the formation of students' attitudes of discipline and responsibility is carried out through the example of teachers in daily behavior, habituation of religious and school cultural activities, giving appreciation and educational reprimands, and continuous communication between teachers and parents. The example of teachers is the main factor in internalizing character values, while habituating activities such as 3S, prayer before learning, and congregational Zuhur prayers play a role in fostering students' discipline and a sense of responsibility consistently. Giving appreciation and reprimands is carried out to strengthen positive behavior and correct violations in an educational manner. However, this study also found that there are obstacles in character development, especially the influence of mobile phone use and the family environment and student associations that are less supportive. This study concludes that the formation of character discipline and responsibility requires a sustainable strategy and synergy between schools and families so that character values can be optimally internalized in students.